(3HQeLI GdeRhOGJs - (3eQGO(B, (3TdHGjIs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2002)
(3ebOeI Edi dZI (BPerl(3;CfhGY GdHjGfGJ aj dZI (BPerl(3,CfhGY GdeTZdGJ aj dZI (BPerl(3,Led GdTQW hGdOhQGf,eWGHbI GdCfeGW,GdbhGFe (BList(3,GdeUahaGJ GdGQJHGWjI,GdHQeLI GdaQYjI,GdedaGJ (BFiles(3,CSGSjGJ HQeLI (BCGI(3,GdGJUGd Hjf GdeJUaM hGdeRhO,GdfeGPL,JTajQ GdHjGfGJ,JWHjbGJ Gd(BCGIs
(3HjHdjhZQGajG U(B.456s
Keywords: (3GdHQeLI GdBdjIs; (3HQGeL GdMGSHGJs